Komik burung surga sebagai media literasi dan penguatan pendidikan karakter di SMP - Ni'mah, Azzahra Nurhidayati; Rohmadi, Muhammad; Rakhmawati, Ani (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2022)
The implementation of education does not only focus on academic aspects, but also emphasizes the character of students. Issues concerning the character of students need to be given serious attention. The purpose of this study is to describe and explain the use of the Burung Surga (Bird of Heaven) comic as a medium for literacy and strengthening character education in junior high schools. The research is a qualitative descriptive study with content analysis method. The object used is a comic entitled Burung Surga. Data analysis was carried out qualitatively. The results showed that there is a content of character education values in Burung Surga comic, including religious, creative, communicative, curiosity, love to read, respect for achievements, social care, responsibility, environmental care, national spirit, and love for the homeland. Through the content of character education values and information in the comic, Burung Surga comic, can be used as a literacy medium in the School Literacy Movement (GLS) program and strengthening character education in junior high schools.